Numerical accuracy of method of false position - Srivastava, R B; Dixit, Narendra Deo (International Multidisciplinary Research Journal, 2012)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin;} --> <!--[endif] --> A computer program in C++ language has been developed to calculate square roots of numbers from 1 to 25 in interval [0, 6] using method of false position. Accuracy of method of false position has been found out in each calculation. Lowest percentage error has been obtained in the calculation of square root of 24 in the interval [0, 6] using method of false position and is equal to 0.000006094208.Â  Highest percentage error has been obtained in the calculation of square root of 1 in the interval [0, 6] and is equal to 0.000399351100. Average percentage error in method of false position in the calculation of square roots of natural numbers from 1 to 25 has been found to be 0.000051494950. Average percentage error of bisection method in the calculation of square roots of natural numbers from 1 to 25 has been found to be 0.000041549568 which indicates that the accuracy of bisection method is greater than that of the method of false position.